Design and Modeling of Mechanical Systems - II Proceedings of the Sixth Conference on Design and Modeling of Mechanical Systems, CMSM'2015, March 23-25, Hammamet, Tunisia - Chouchane, Mnaouar; Fakhfakh, Tahar; Daly, Hachmi Ben; Aifaoui, Nizar; Chaari, Fakher (Lecture Notes in Mechanical Engineering,, 2015)
This book offers a collection of original peer-reviewed contributions presented at the 6th International Congress on Design and Modeling of Mechanical Systems (CMSM'2015), held in Hammamet, Tunisia, from the 23rd to the 25th of March 2015. It reports on both recent research findings and innovative industrial applications in the fields of mechatronics and robotics, dynamics of mechanical systems, fluid structure interaction and vibroacoustics, modeling and analysis of materials and structures, and design and manufacturing of mechanical systems. Since its first edition in 2005, the CMSM Congress has been held every two years with the aim of bringing together specialists from universities and industry to present the state-of-the-art in research and applications, discuss the most recent findings and exchange and develop expertise in the field of design and modeling of mechanical systems. The CMSM Congress is jointly organized by three Tunisian research laboratories: the Mechanical Engineering Laboratory of the National Engineering School of Monastir; the Mechanical Laboratory of Sousse, part of the National Engineering School of Sousse; and the Mechanical, Modeling and Manufacturing Laboratory at the National Engineering School of Sfax.